Walter B. Wriston being sworn in as Chairman of President Ronald Reagan's Economic Advisory Board (Tufts Archival Research Center, 2008)
7.4 x 8.8. Also pictured, George P. Shultz. The print and digital image were created from 'File2805' from the CD titled 'Walter B. Wriston Photographs - CD 1'.